Intergenerational Partnership in Research and Development Activity - Gheorghe Zaman; Steliana Sandu; Irina Anghel (Amfiteatru Economic Journal, 2009)
The emergence, spreading and dissemination of scientific knowledge currently surpasses the capacity of assimilation and processing by one individual, requiring multidisciplinary and multigenerational team research. The need of interaction and networking uptakes more and more in the management of research-development and innovation (RDI) due, on the one hand, to the growth of its complexity in the knowledge-based economy and, on the other hand, to the urgent need of researchers to come up with solutions for the pressing socio-economic issues. International experience proves that high individual professional quality is not enough for a successful research team. It requires collaboration, including an efficient intergenerational partnership acting in a working environment based on responsibilities, merit acknowledgement, risk-taking, kindness, support, good standards, conflict-avoidance (except for conflicts of ideas) as well as on the scientific identity of every researcher, irrespective of their age. Recognition of scientific and managerial complementarities of the research team members and reciprocal respect for personal values ensures the most efficient valorization of researchers potential within the team. The appreciation and recognition given to the collaborative work are important factors for creativity and success, given the positive relationship between these factors and the quality and quantity of the research output. The research and development (R&D) activity performance is greater when decisions, objectives and priorities are collectively established, since research activity is no more an individual effort, but a consequence of team work contribution. The paper presents the research results regarding the way in which the above mentioned aspects are reflected in R&D intergenerational partnership in Romania, revealing its typology and characteristics, the age structure trends of research teams, as well as the factors that stimulate or hinder cooperation between young researchers and the more experienced ones.
Keywords: O32; O39; O38; J24; 330; intergenerational partnership; research-development; efficient teams; scientific complementarity